2022
DOI: 10.1002/sstr.202200221
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Real Charge Carrier in Aqueous Zinc Batteries Based on Polythiophene/Manganese Dioxide Cathode

Abstract: Developing sustainable and clean energy (solar, wind, tidal energy, etc.) is a significant way to solve the increasing energy crisis and environmental problems. [1,2] However, sustainable and clean energies are difficult to stabilize supply due to their significant instability and randomness, which require grid-scale energy storage equipment to achieve stable and continuous energy output. [3][4][5] Benefiting from the high energy density and long cycling life, the energy storage market is dominated by lithium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Interestingly in both electrodes, the first three CV curves almost overlap, implying the superior structural stability of TiS 2 upon Zn 2+ insertion/extraction. 49 Figure 3b presents the original charge/discharge profiles drawn by both TiS 2 and D-TiS 1.94 from 0.05 to 0.7 V (vs Zn 2+ /Zn) at 0.05 A g −1 . Both cathodes exhibit three distinct discharge/charge voltage plateaus, agreeing well with the CV redox peaks in Figure 3a, which is related to the multiple Zn 2+ insertion/extraction processes at different sites.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly in both electrodes, the first three CV curves almost overlap, implying the superior structural stability of TiS 2 upon Zn 2+ insertion/extraction. 49 Figure 3b presents the original charge/discharge profiles drawn by both TiS 2 and D-TiS 1.94 from 0.05 to 0.7 V (vs Zn 2+ /Zn) at 0.05 A g −1 . Both cathodes exhibit three distinct discharge/charge voltage plateaus, agreeing well with the CV redox peaks in Figure 3a, which is related to the multiple Zn 2+ insertion/extraction processes at different sites.…”
Section: Resultsmentioning
confidence: 99%
“…However, the electrochemical performance of δ-MnO 2 in AZIBs is severely limited by sluggish reaction kinetics, inferior structural stability, intense electrostatic interactions, and poor electronic conductivity. 7 To overcome these problems, researchers have proposed various strategies, including nanostructure design, 8,9 composites with conductive polymers, 10 preintercalation, 11−15 and defect engineering, 16 to improve the electrochemical performance of δ-MnO 2 cathodes. In particular, the preintercalation strategy has proven to be a fundamental and highly effective approach for enhancing the capacity, cycle stability, and rate capability of a δ-MnO 2 cathode.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, researchers have proposed various strategies, including nanostructure design, , composites with conductive polymers, preintercalation, and defect engineering, to improve the electrochemical performance of δ-MnO 2 cathodes. In particular, the preintercalation strategy has proven to be a fundamental and highly effective approach for enhancing the capacity, cycle stability, and rate capability of a δ-MnO 2 cathode. , Preintercalated ions or molecules play a crucial role in increasing the interlayer spacing, facilitating ion transfer, and serving as “structural pillars” to prevent structural collapse. Meanwhile, preintercalation can efficiently fine-tune the electronic structure of the host materials, leading to significant acceleration of electron-transfer processes. Various ions and molecules have been previously investigated, including alkali ions, , NH 4 + , tetramethylammonium, Cu 2+ , Zn 2+ , Ba 2+ , La 3+ , Sn 4+ , Mo 4+ , and polyaniline .…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Nevertheless, the research of high-performance MnO 2 still encounters significant barriers due to its structural instability and manganese dissolution, impeding its actual applications. To solve these issues, tremendous efforts, such as heteroatoms doping, 35−37 surface engineering, 38 defect engineering, 39,40 and electrolyte modification, 41−43 have been devoted to improving its electrochemical performance. Heteroatoms doping can enhance the stability of manganese dioxide skeleton and avoid excessive dissolved deposition of manganese dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…It is more favorable to give higher capacity than MnO 2 with other crystalline forms. , Nevertheless, the research of high-performance MnO 2 still encounters significant barriers due to its structural instability and manganese dissolution, impeding its actual applications. To solve these issues, tremendous efforts, such as heteroatoms doping, surface engineering, defect engineering, , and electrolyte modification, have been devoted to improving its electrochemical performance. Heteroatoms doping can enhance the stability of manganese dioxide skeleton and avoid excessive dissolved deposition of manganese dioxide. , Since the atomic radius of Al 3+ (53.5 pm) is comparable to that of Mn 4+ (53 pm), it has been suggested that aluminum can replace Mn or occupy the tunnels of MnO 2 more easily. Furthermore, it is reported that aluminum doping can also increase the conductivity of manganese dioxide …”
Section: Introductionmentioning
confidence: 99%